2017
DOI: 10.15616/bsl.2017.23.3.201
|View full text |Cite
|
Sign up to set email alerts
|

Association of Uric Acid Levels with Arterial Stiffness in Korean Women and Non-smoking Men

Abstract: Measuring the pulse wave velocity (PWV) is a non-invasive method for evaluating the stiffness of the vessel wall. While previous studies investigated the association of uric acid level with arterial stiffness, most did not consider smoking status and obesity as covariates. The objective of this study was to investigate the relationship between uric acid levels and arterial stiffness, considering smoking status and obesity. We studied 3390 subjects (1940 males and 1450 females). Abnormal PWV was also defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…This relationship was observed in women and only in nonsmoking men with normal blood pressure. 70 However, several studies reported no association between UA and arterial stiffness.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…This relationship was observed in women and only in nonsmoking men with normal blood pressure. 70 However, several studies reported no association between UA and arterial stiffness.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%